Feasibility and acceptability of a future‐oriented empowerment program to prevent substance use and school dropout among school‐disengaged youth. Issue 2 (16th January 2020) - Stoddard, Sarah A.; Hughesdon, Kathryn; Khan, Angubeen; Zimmerman, Marc A.
Abstract: Objective: To evaluate the feasibility and acceptability of a health promotion program to prevent school dropout and substance use among middle school‐aged youth who display early warning signs of school disengagement. Intervention: Youth Empowerment Solutions for Positive Futures (YES‐PF), an intensive, theoretically driven, 5‐week summer enrichment program, aims to prevent school dropout and substance use by promoting youth empowerment, school engagement, and future orientation. Design and Sample: Using a pre–post‐intervention design, we test feasibility and acceptability with 6th and 7th grade students ( n  = 43) who exhibited early warning signs for school disengagement (e.g., chronic absenteeism) in two school districts. Measures: Program evaluation components included: (a) program session forms completed by facilitators; (b) post‐program interviews with facilitators; (c) post‐intervention program evaluation surveys with youth; (d) attendance; and (e) baseline and post‐intervention surveys with youth to assess behavioral and psychosocial outcomes. Results: Facilitators routinely delivered core component lesson activities. Acceptability and program satisfaction were evidenced in strong program attendance by youth. Youth participants reported higher levels of leadership efficacy ( p  < .05) and a greater sense of control over their lives and potential problems ( p  < .01). Conclusions: YES‐PF was feasible and acceptable to school personnel and youth. Program refinement, based on implementation findings, is discussed.